Economic analysis in healthcare - Morris, Stephen 1953-; Devlin, Nancy; Parkin, David; Spencer, Anne (Wiley, 2012)
Economic Analysis in Health Care, Second Edition is intended as a core textbook for advanced undergraduate and postgraduate students of health economics. The authors provide comprehensive coverage of the field of economics in health care and the evaluation of health care technologies. This new edition has been fully updated with up-to-date case studies from the UK, Europe and the Rest of the World.  It includes a new chapter on health care labour markets and contains new material integrated throughout the text on the economics of public health. Adopts an international perspective towards topics in health economics Creates a useful balance of theoretical treatment and practical application throughout the book Focuses on both market-related and economic evaluation aspects of health economics